Design like nature : biomimicry for a healthy planet - Clendenan, Megan, 1977-; Woolcock, Kim Ryall (Orca footprints., 2021)
Explores the concept of biomimicry, the scientific term for when we learn from and copy nature, and explains how we can use it to solve environmental problems such as climate change. Highlights historical and present-day applications of biomimicry. Includes color photographs, fact boxes, a glossary, and additional resources.